2012
DOI: 10.1097/bcr.0b013e3182331e73
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Organ Failure as a Cause of Death in Patients With Severe Burns

Abstract: The aim of this study was to investigate the causes of death in patients with burns using both medicolegal autopsy reports and clinical data collected during treatment to specify irreversible organ dysfunctions leading to death. Burn deaths occurring in the Helsinki Burn Center from 1995 to 2005 were identified in the hospital database. The clinical charts and medicolegal autopsy reports were retrieved and compared. The data were evaluated by plastic surgeons specialized in burn care, an intensivist, and a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 21 publications
3
61
0
2
Order By: Relevance
“…This enhances the appearance and proliferation of multiresistant bacteria and increases costs. Conversely, failure to apply early and appropriate antibiotic treatment for suspected infection is widely demonstrated to be associated with a worse prognosis in all patient groups (5)(6)(7)21). Therefore, the incorporation of PCT analysis, as an objective biomarker of infection in burn patients, would lower antibiotic exposure, reduce unneeded rotations of vascular access, and decrease the number of requested microbiological determinations, both invasive and noninvasive.…”
Section: Discussionmentioning
confidence: 99%
“…This enhances the appearance and proliferation of multiresistant bacteria and increases costs. Conversely, failure to apply early and appropriate antibiotic treatment for suspected infection is widely demonstrated to be associated with a worse prognosis in all patient groups (5)(6)(7)21). Therefore, the incorporation of PCT analysis, as an objective biomarker of infection in burn patients, would lower antibiotic exposure, reduce unneeded rotations of vascular access, and decrease the number of requested microbiological determinations, both invasive and noninvasive.…”
Section: Discussionmentioning
confidence: 99%
“…62 The principal causes of death in Sweden are cardiovascular disorders and cancer 100 and, among those with burns, multiple organ failure. 101,102 In our third study, we showed that the causes of death in most patients who died with a low Baux score were not directly related to the burn, and therefore they cannot be predicted by models of burn-specific mortality.…”
Section: Unpredictable Deathsmentioning
confidence: 97%
“…[1,3,9,10] In developed countries, on the other hand, such deaths are more common among children and the elderly. [7,11] This age difference can be explained by the implementation of more effective preventive measures and greater availability of treatment options in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The comparison of antemortem and postmortem findings has revealed differences between antemortem clinical diagnoses and autopsy findings. [6][7][8] Autopsy may show unexpected or unrecognized clinical findings, and the data obtained from autopsy can be used to elucidate future problems experienced by the patients.…”
mentioning
confidence: 99%